Perceptions of Malaysians of the market potential of dark tourism / Obrain Anak Mang ... [et al.] - Mang, Obrain; Halid, Mohd Zuqhairy Khan; Robot, Nickolen; Bidder, Christy; Rainanto, Bambang Hengky (Universiti Teknologi MARA, Sabah, 2024)
This past decade marks a significant growth of dark tourism with an increasing number of dark tourists. In Malaysia, despite the seemingly enormous potential of developing dark tourism in the country, dark tourism sites in Malaysia are not globally recognized yet and cannot attract international tourists. Against this backdrop, this study aimed to analyze the market potential of dark tourism in Malaysia. Specifically, the study's objectives were i) to examine the locals’ general understanding of dark tourism in Malaysia and ii) to analyze the locals' acceptance and perception of the market potential of dark tourism in Malaysia. The research was a quantitative, descriptive, and cross-sectional study. The research instrument was an online survey posted on such platforms as WhatsApp, Facebook, and Instagram. Three hundred fifty six survey responses were used for descriptive analysis (frequencies, means, and standard deviations). The study’s key findings reveal that while local Malaysians may have previously heard about dark tourism, they lack a conceptual grasp of the phenomenon; that is, they primarily associate dark tourism with supernaturalism and entertainment and not the other more purposeful aspects of dark tourism (i.e., education, patriotism, commemoration, and spirituality). Moreover, local Malaysians may have an enthusiastic acceptance of dark tourism and a positive outlook on the potential of developing and promoting this niche tourism in Malaysia as long as dark tourism serves economic, entertainment, and educational purposes. The study was particularly significant from a managerial perspective because its findings could be beneficial for tourism developers and operators to understand the marketability of dark tourism in Malaysia and, subsequently, assist them in developing appropriate and innovative tourism products that tap into this market potential. The study ended with an acknowledgment of the study's limitations and a suggestion for future research.